2003
DOI: 10.1034/j.1600-0404.2003.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Microembolic signals and carotid plaque morphology: a study of 71 patients with moderate or high grade carotid stenosis

Abstract: MES+ patients presented a significantly increased frequency of anechogenic/hypoechogenic plaques. As MES may be a marker of increased risk of stroke, the clinical significance of this particular association should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…MES detected by TCD have been reported in symptomatic carotid disease and are associated with an increased risk of stroke. 19 -22 Many studies correlated MES to more severe degrees of carotid stenosis, 23,24 but only a few have suggested the association of MES to morphological, as opposed to biological, features of plaque instability, such as ulcerated appearance on angiography, 22,25 an echolucent appearance on ultrasonography, 26 or plaque ulceration and surface thrombus on histological examination. 27 On the other hand, several discrepant studies 4,28,29 failed to find an association between MES and macroscopic plaque characteristics, including intraplaque hemorrhage, adherent thrombus, and surface ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…MES detected by TCD have been reported in symptomatic carotid disease and are associated with an increased risk of stroke. 19 -22 Many studies correlated MES to more severe degrees of carotid stenosis, 23,24 but only a few have suggested the association of MES to morphological, as opposed to biological, features of plaque instability, such as ulcerated appearance on angiography, 22,25 an echolucent appearance on ultrasonography, 26 or plaque ulceration and surface thrombus on histological examination. 27 On the other hand, several discrepant studies 4,28,29 failed to find an association between MES and macroscopic plaque characteristics, including intraplaque hemorrhage, adherent thrombus, and surface ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests an association between plaque morphology and solid embolization, which supports the results of previous studies in which an association was found between plaque morphology and ischemic stroke. 15,24,25 …”
Section: Discussionmentioning
confidence: 99%
“…Emboli detection has also been suggested as a method to flag up asymptomatic patients (ACS) for surgical intervention (Spence et al 2005). For patients with moderate to high grade stenosis, emboli were more prevalent in patients with hypoechoic plaques and this may carry potential clinical relevance (Mayor et al 2003a). Further study is required as only a low number of patients (71) were used in this study.…”
Section: Ultrasound Techniquesmentioning
confidence: 99%